Endodontic management of maxillary first molar with protostylid: a rare case report - Yang Zhou; Ye Tao (BMC, 2023)
Abstract Background A protostylid is a relatively rare dental developmental aberration characterized as an extra cusp located on the mesial half of the buccal surface of the molars. A protostylid is rarely to be reported due to its low rate of occurrence. This case report describes a patient referred for endodontic treatment due to the presence of a protostylid on the buccal surface of the maxillary first molar that induced apical periodontitis. Case presentation A 53-year-old female reported a 3-month history of pain of chewing with her upper left posterior teeth over 3 months. In the clinical examination, an abraded anomalous cusp-like structure was found on the buccal surface of tooth 26, Cone beam computed tomography (CBCT) revealed a supernumerary cusp with an intact root canal inside, which was fused with the mesiobuccal (MB) root canal in the middle of the root. In addition, extensive periapical radiolucency was observed around tooth 26. The tooth was diagnosed as apical periodontitis, and endodontic treatment was performed. The initial lesion in tooth 26 gradually healed over 1 year of observation. Conclusions To our knowledge, this case is the first to describe the endodontic management of a maxillary first molar with a protostylid and advances our understanding of supernumerary cusps. This case provides a reference for the treatment of protostylid.